REVIEW IOT CYBERSECURITY: EMERGING RISKS AND MITIGATION APPROACHES – A COMPREHENSIVE SURVEY - Dilmurod Mirzaaxmedov (Modern American Journals, 2025)
The Internet of Things (IoT) is increasingly integrated into everyday life, bringing with it serious cybersecurity concerns and a growing demand for robust protection mechanisms. This study presents a comprehensive systematic review of recent literature, examining the key challenges and types of cyberattacks that compromise IoT security. It evaluates existing frameworks and solutions while identifying emerging trends and notable research gaps. A distinguishing aspect of this work is its focused analysis of machine learning techniques employed to detect and mitigate IoT-related threats. Furthermore, the study highlights underexplored areas such as the economic implications of IoT vulnerabilities and specific security challenges within industrial IoT environments. The review synthesizes insights from relevant academic sources and outlines potential directions for future research. Findings suggest that privacy breaches and cybercrime remain the most critical concerns in IoT security. Although artificial intelligence shows significant promise in enhancing future defenses, certain threats—such as confidentiality violations, authentication failures, and insecure data server connections—are still insufficiently addressed by current approaches. This underscores the need for continued research and real-world validation of proposed solutions. As IoT technologies evolve rapidly, the importance of proactive cybersecurity strategies becomes increasingly evident. Greater international collaboration among cybersecurity stakeholders is essential to establish new standards and practices capable of addressing the unique vulnerabilities inherent in IoT systems.
Keywords: Internet of Things (IoT); cybersecurity; cybersecurity frameworks; cybersecurity approaches.